PL.26 Validation of a Formative Assessment Tool for Vacuum Delivery. (26th April 2013) - Bahl, R; Murphy, DJ; Strachan, BK
Abstract : Introduction: Operative vaginal delivery is one of the first operative procedures a trainee obstetrician performs independently. Competence is developed through work place experience and formative feedback in the form of OSATS. In OSATS each subtask is classified as 'competent' or 'needs help' with a global rating scale to support the assessment. We have developed a formative assessment tool that is likely to aid the feedback by classifying each subtask into five skill levels. Aim: To ascertain the construct validity of a new formative assessment tool. Method: Twenty three videos of vacuum delivery conducted by 10 expert (ST6 and above) and 13 novice (ST1 and ST2) obstetricians were recorded. The video recordings were anonymised and reviewed by a senior obstetrician using the formative assessment tool to score the video recording. There were a total of 12 subtasks, each scored between one and five. Results: The mean score for the experts was 48.4 (80.6%) compared to the mean score for novices of 34.6 (57.7%). The students T test result was significant at 5.01 with p value of <0.001 and 95% confidence intervals of 8.6 to 19.1. The average median score for experts was 4.8 and for novices was 3.3. Discussion: The above findings show that the formative assessment tool for vacuum extractor delivery has construct validity and is able to differentiate between an expert and a novice. We believe that the detailed feedback using this assessment tool will facilitate greater understanding of the skills required to develop expertise in vacuum extractor delivery.